USING INFOGRAPHIC IN TEACHING BASIC JAPANESE - Hoi, Huynh Tan (International Journal of Psychosocial Rehabilitation, 2020)
Designing effective methods of teaching and transmitting messages is one of the keys to help teachers improve the effectiveness of teaching subjects in general and Japanese in particular. Originating from this practice, the use of infographic helps students grasp the basic knowledge of the subject because infographic is very popular with young people. This is seen as a way to convey ideas and complex information with visual images. These designs provide complex information in a concise, clear form by symbols, symbols, maps, colors, articles. The article deals with the application of infographic in Japanese language teaching with the aim of helping students easily remember important knowledge. The content of the course is thought that the heavy will become less boring, awakening the interest of young people, instead of complicated formulas or words presented through many pages.